On the Nature of the Dark Cavity of Solar Coronal Mass Ejections - Hongqiang Song; Leping Li; Bing Wang; Lidong Xia; Yao Chen (The Astrophysical Journal, 2024)
Earlier studies have shown that less than one-third of coronal mass ejections (CMEs) possess the archetypical three-part (bright core, dark cavity, and bright front) structure in the outer corona (e.g., 2–6 R _⊙ ). In the traditional opinion, the core, cavity, and front correspond to the erupted filament, magnetic flux rope (MFR), and plasma pileup along the MFR border, respectively. Recent studies have demonstrated that nearly 100% of normal CMEs have a three-part structure in the inner corona (<2 R _⊙ ), agreeing with the prediction of a new explanation of the nature of the three-part structure. In the new opinion, the core and front correspond to the MFR plasma and plasma pileup along the coronal loops, respectively. The cavity is either a part of the MFR, or a low-density zone between the front and the MFR. In this paper, we revisit a textbook case of an eruption that occurred on 2017 September 10. In the inner corona, the CME exhibited a clear three-part appearance in the extreme-ultraviolet images and had a smooth-curved front, while, in the outer corona, the CME loses the three-part feature as the core expands and the cavity disappears. Meanwhile, a bulge appears at the CME front as the core moves faster than the front and protrudes from its bottom. It is difficult to understand the disappearance of the cavity and the appearance of the bulge if assuming the cavity as being a part of the MFR. Therefore, we suggest that the dark cavity represents a low-density zone between the front and MFR in the early eruption stage.